2019
DOI: 10.1186/s40246-019-0198-2
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive prenatal testing for chromosome aneuploidies and subchromosomal microdeletions/microduplications in a cohort of 8141 single pregnancies

Abstract: BackgroundNoninvasive prenatal testing (NIPT) for fetal aneuploidies by scanning cell-free fetal DNA in maternal plasma is rapidly becoming a first-tier aneuploidy screening test in clinical practices. With the development of whole-genome sequencing technology, small subchromosomal deletions and duplications that could not be detected by conventional karyotyping are now able to be detected with NIPT technology.MethodsIn the present study, we examined 8141 single pregnancies with NIPT to calculate the positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(82 citation statements)
references
References 43 publications
7
69
4
2
Order By: Relevance
“…Therefore, genetic counseling combined with serum biochemical screening and ultrasound detection of abnormalities, should be fully carried out for advanced-age pregnant women. The incidences of 45,X and 47,XYY were signi cantly correlated with maternal age, whereas those of 47,XXX and 47,XXY did not show signi cant correlations [5,35] . Although there was no statistical signi cance between the incidence of 47,XYY and the maternal age, but it observed that the incidence of 47,XYY decreased with maternal age in the advanced aged group.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Therefore, genetic counseling combined with serum biochemical screening and ultrasound detection of abnormalities, should be fully carried out for advanced-age pregnant women. The incidences of 45,X and 47,XYY were signi cantly correlated with maternal age, whereas those of 47,XXX and 47,XXY did not show signi cant correlations [5,35] . Although there was no statistical signi cance between the incidence of 47,XYY and the maternal age, but it observed that the incidence of 47,XYY decreased with maternal age in the advanced aged group.…”
Section: Discussionmentioning
confidence: 74%
“…Our study showed that NIPT performed better in predicting sex chromosome trisomies than monosomy X. This is potentially because the low guanosine-cytosine content of the X chromosome leads to highly variable ampli cation of the X chromosome, as well as the occurrence of age-related X chromosome loss in normal female white blood cells [5] . The PPV of SCA is lower than other common chromosome aneuploidy.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations